The performance of elements of a 'level of response to alcohol'-based model of drinking behaviors in 13-year-olds. - Schuckit MA; Smith TL; Trim R; Heron J; Horwood J; Davis JM; Hibbeln JR (Addiction, 2008)
AIM: The goals of this paper are to evaluate whether drinking practices among peers mediates the relationship between a low level of response (LR) to alcohol and a person's heavier drinking and alcohol-related problems in 12-14-year-olds. DESIGN: Correlations and structural equation models (SEM) were used to test a hypothesized model of the relationships among key variables in adolescents from the Avon Longitudinal Study of Parents and Children (ALSPAC), a longitudinal birth cohort study in Bristol, England. PARTICIPANTS: These included 688 boys (40.4%) and girls who were offspring of the pregnant women who had been selected as ALSPAC participants in 1991 and 1992. The offspring were interviewed at about age 13 years, and those who had ever consumed a full drink completed the Self-Report of the Effects of Alcohol (SRE) questionnaire indicating the number of drinks required for up to four effects early in their drinking histories. A higher number of drinks required for effects indicated a low LR per drink consumed. FINDINGS: The SEM explained 58% of the variance of the alcohol pattern, and had good fit characteristics. A low LR was related to heavier drinking and more alcohol problems both directly and as mediated partially by drinking in peers. The model performed well across the narrow age range, and applied equally well in boys and girls. CONCLUSIONS: The perceived drinking practices of peers is a potentially important mediator of how a low LR to alcohol relates to drinking practices during early adolescence. The findings may be useful in developing approaches to prevent heavier drinking in this young group.